Impact of Attributional Style of Behavior Outcome on the Sustainable Development of Residents’ Energy-Saving Behavior: Differences in Policy Responses of Residents - Ting Yue; Jing Zhou; Yingkai Zhang; Mengting Li; Qianru Wang; Ruyin Long; Junli Liu (Applied Sciences, 2023)
In the context of promoting the construction of an energy-saving and environment-friendly society, it is crucial to promote the sustainable development of residents’ energy-saving behaviors, determine how attributional styles of behavior outcome affect residents’ energy-saving behaviors, and examine how different residents respond to intervention policies. Based on the attribution theory, this study constructs a theoretical model of the impact mechanism of the attributional style of behavior outcome on residents’ energy-saving behaviors. Regression analysis and the quadratic response model were used to test all 1254 valid questionnaires. The results show that the residents’ degrees of understanding, support, and implementation of the energy-saving policies presented inconsistent situations. Residents’ degrees of understanding and support of energy-saving policies positively promote the degree of implementation of energy-saving policies. The consistency of understanding and support has a non-linear influence on the degree of implementation of energy-saving policies. Additionally, the public’s understanding, support, and implementation of energy-saving policies have significant differences in the attribution style of behavioral outcomes. Finally, some relevant policy recommendations are put forward.